Analisis Laporan Arus Kas untuk Menilai Kinerja Keuangan PT. Garuda Indonesia (Persero) Tbk pada Periode Tahun 2019-2023 - Juwita Zahirah Azhar (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study evaluates the financial performance of PT. Garuda Indonesia (Persero) Tbk from 2019 to 2023 by analyzing cash flow statements. It employs a descriptive research design with a quantitative approach, utilizing eight cash flow ratios: Operating Cash Flow (AKO), Fund Flow Coverage (CAD), Cash to Interest Coverage (CKB), Cash to Current Liabilities Coverage (CKHL), Capital Expenditure (PM), Total Debt (TH), Cash Flow Adequacy (KAK), and Free Net Cash Flow (AKBB). The analysis reveals that only the Cash to Interest Coverage (CKB) ratio meets the efficiency standard, while the remaining seven ratios consistently fall below it. Consequently, the financial performance of PT. Garuda Indonesia (Persero) Tbk during this period is concluded to be poor.